The effectiveness of self-management training to improve the discipline of students during post covid-19 pandemic - Umam, M. Ulyaul; Sa’adah; Noor, Rifqi Nazahah (Utan Kayu Publishing, 2024)
This study aims to examine the effectiveness of self-management training in improving student discipline at the Tarbiyatul Muttaqin Islamic Boarding School post Covid-19 pandemic. Using an experimental design with a nonequivalent control group, ten students were divided into two groups: an experimental group that received self-management training and a control group that did not receive any intervention. The self-management training comprised four stages: self-monitoring, self-analysis, self-change, and self-maintenance. The primary instrument used was a validated discipline study questionnaire. Data were analyzed using the Wilcoxon test to compare pretest and posttest scores. The analysis showed a significant increase in discipline scores in the experimental group after receiving self-management training. All participants experienced an increase in discipline. This study demonstrates that self-management training effectively improves student discipline through the processes of monitoring, analysis, change, and maintenance. These findings align with previous research showing the effectiveness of self-management training in enhancing student discipline. Practical implications suggest that self-management training can be implemented in Islamic boarding schools to address common disciplinary issues such as tardiness and failure to complete assignments. It is recommended that the positive outcomes from this research be further developed and applied in various educational contexts to enhance student discipline and academic performance. Further research with larger samples and randomized designs is needed to strengthen these findings.